Mortality assessment of patients with hepatocellular carcinoma according to underlying disease and treatment modalities. Issue 9 (March 2017) - Golabi, Pegah; Fazel, Sofie; Otgonsuren, Munkhzul; Sayiner, Mehmet; Locklear, Cameron T.; Younossi, Zobair M.
Abstract : Abstract: Hepatocellular carcinoma (HCC) is among the most common types of cancer. Liver transplantation (LT) and surgical resection (SR) are primary surgical treatment options for HCC. The aim of the study was to assess mortality within 2 years postdiagnosis among patients with HCC according to their treatment modalities. We examined data from the Surveillance, Epidemiology and End Results (SEER)-Medicare database between 2001 and 2009. SEER registries collect demographics, cancer stage and historical types, and treatments. Medicare claims include diagnoses, procedures, and survival status for each beneficiary. Patients with HCC were identified using the International Classification of Disease Oncology, Third Edition Site code C22.0 and Histology Code 8170-8175. Treatment modalities were LT, SR, or nonsurgical treatment. Total of 11, 187 cases was included (age at diagnosis: 72 years, 69% male, 67% White). HCC patients who underwent LT were younger (61 vs 71 years), sicker (presence of decompensated cirrhosis: 80% vs 23%), and less likely to die within 2 years (29% vs 44%, all P < 0.01), compared to SR patients. In multivariate analysis, older age (HR: 1.01 [95% CI = 1.01–1.01]), stage of HCC other than local (HR: 1.81[95%CI = 1.70–1.91]), and being treated with SR (HR: 1.95 [95%CI = 1.55–2.46]) were independent predictors of mortality within 2 years. Furthermore, the presence of decompensated cirrhosis (HR: 1.84 [95%CI = 1.73–1.96]) and alcoholic liver disease (HR: 1.19[95%CI = 1.11–1.28]) increased within 2 years mortality. Mortality within 2 years postdiagnosis of HCC was significantly higher in patients treated with SR than LT. Abstract : Supplemental Digital Content is available in the text